1996
DOI: 10.1111/1523-1747.ep12338544
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Mast Cell Activation by Autoantibodies Against the High Affinity IgE Receptor in Chronic Urticaria

Abstract: Previous studies identified autoantibodies against the IgE high affinity receptor alpha-chain, Fc epsilon RI alpha, in sera of selected patients with severe chronic idiopathic urticaria. We have now determined the incidence of anti-Fc epsilon RI alpha autoantibodies in a group of 163 patients. Intradermal injection of autologous serum caused skin reactions indicative of mast cell degranulation in 98 (60%) patients. Based on histamine release from IgE-sensitized and nonsensitized basophil leukocytes of healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
244
1
8

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(260 citation statements)
references
References 15 publications
7
244
1
8
Order By: Relevance
“…However the autoantibodies were only detected in some, but not all of the patients with the positive skin tests. This might indicate that IgE stimulates their mast cells, although further examination would be needed (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…However the autoantibodies were only detected in some, but not all of the patients with the positive skin tests. This might indicate that IgE stimulates their mast cells, although further examination would be needed (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…This work was initiated, as in our case, by careful clinical observation, namely the reactivity of chronic urticaria patients to their own serum after its local injection into their skin, resulting in a typical wheal and flare reaction (19). The same group of investigators showed thereafter that 141 about 30% of their patients with chronic urticaria exhibited these reactions and contained IgG antibodies causing in vitro histamine release from skin slices (20)(21)(22). About 80% of these antibodies were found to be directed against the a chain of the high affinity IgE membrane receptor (FceRIa) and the remainder against IgE (22,23).…”
Section: Autoimmune Mechanisms As a Cause Of Chronic Urticariamentioning
confidence: 92%
“…The same group of investigators showed thereafter that 141 about 30% of their patients with chronic urticaria exhibited these reactions and contained IgG antibodies causing in vitro histamine release from skin slices (20)(21)(22). About 80% of these antibodies were found to be directed against the a chain of the high affinity IgE membrane receptor (FceRIa) and the remainder against IgE (22,23). Roughly 31% of chronic urticaria patient sera apparently contain additional histamine releasing activity of unknown nature (21).…”
Section: Autoimmune Mechanisms As a Cause Of Chronic Urticariamentioning
confidence: 99%
“…Bu çalışma sonucunda ayrıca OSDT pozitifliği olan hastaların Konstantinou ve arkadaşlarının 25 belirttiği gibi tiroid patolojileri açısından araştırılması gerektiği ifade edilmiştir 22 . Son yayınlarda KÜ tanılı olguların %23-40 kadarında yüksek afiniteli IgE reseptörüne karşı IgG yapısında otoantikorlar saptanmış 26,27 olup, ilave olarak %5-9 kadarında da fonksiyonel anti IgE antikorları saptanmıştır 27,28 . Bu durum kronik otoimmun ürtiker (KOÜ) olarak ifade edilmektedir.…”
Section: Discussionunclassified